Nutrition and feeding of organic cattle [ - Blair, Robert , 1933- (CABI, 2011)
The practice of organic cattle farming has continued to increase in recent years, backed by consumer demand, organisations and governments. Beginning with an overview of the aims and principles behind organic cattle production, this book presents compreensive information about how to feed cattle so that the milk and meat produced meet organic standards. "Nutrition and Feeding of Organic Cattle" provides a comprehensive summary of ruminant digestive processes and nutrition. The author, past-President of the World Association for Animal Production, utilises years of animal nutrition experience to describe the effects of feeding programmes using approved organic ingredients on cattle productivity, health and welfare. The book also provides up-to-date information on consumer aspects of organic meat and milk, and on production of greenhouse gases by cattle raised organically. It is suitable for producers, researchers, lecturers, regulatory agencies, feed manufacturers, food producers and veterinarians.